Contactless silicon-based multi-dimensional Hall sensor with simultaneous magnetic sensing and omni-rotational angle measurement - Kaewjumras, Yongyut; Prabket, Jirawat; Titiroongruang, Wisut; Niemcharoen, Surasak (My University, 2019)
This experimental research proposes a contactless silicon-based two-dimensional (2D) Hall sensor capable of simultaneous parallel- and perpendicular-directional magnetic sensing, with a 360° angle measurement. The Hall sensor was of non-symmetrical five-ohmic contact configuration (C1 – C5). In the study, experiments were carried out in three stages. In the first-stage experiment, the current (I) and voltage (V) of the 2D Hall sensor were determined under three schemes: schemes A (C1&C2), B (C2&C5), and C (C3&C4). In the second-stage experiment, the parallel and perpendicular absolute sensitivities of the 2D sensor were examined. Considering the discrepancy between the parallel and perpendicular absolute sensitivities, signal conditioning circuitry was incorporated into the sensor system to compensate, and the rotational angles measured in the final-stage experiment. The results revealed that the I-V curves were dominantly linear, corresponding to Ohm’s law. However, the parallel and perpendicular absolute sensitivities were low and unequal. Thus, signal conditioning circuitry was incorporated into the system to address the discrepancy and improve the performance. Importantly, the 2D Hall sensor exhibited a mere ±3o discrepancy between the measured and reference rotational angles, given the magnetic flux density of 1000 G, with the hysteresis error of 2.8%. In essence, the proposed contactless silicon-based 2D Hall sensor possesses high potential for high-precision industrial applications.
Keywords: Angle; Contactless; Conventional hall plate; Hall effect; Magnetic sensor